Hanaq Pacha: Ein Gräberfeld der Nasca-Zeit und des Mittleren Horizontes in Palpa, Peru - Fux, Peter (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
In this article, twenty mostly intact burial contexts, including their complete inventory of artifacts, found at the site of Hanaq Pacha at Palpa, Peru, are presented. Only very few intact burial contexts from the Nasca culture (200 B.C. – 650 A.D.) have been documented and published so far. On the basis of the ceramic vessels, the burials of Hanaq Pacha can stylistically be dated into the Middle Nasca Period (Phase 5, approx. 330 – 430 A.D.). According to the ceramic offering of one of the funerary contexts, this tomb dates to the Middle Horizon (650 – 1000 A.D.). Of particular interest are the re-openings of some Nasca burials during the Middle Horizon, obviously for the purpose of introducing additional offerings as well as human bodies. A more detailed cultural and historical discussion of these fi ndings is intended to be delivered in future publications.The article will be available as a PDF in the near future.